mhbounds: Sensitivity Analysis for Average Treatment Effects - Sascha O. Becker; Marco Caliendo (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Matching has become a popular approach to estimate average treatment effects. It is based on the conditional independence or unconfoundedness assumption. Checking the sensitivity of the estimated results with respect to deviations from this identifying assumption has become an increasingly important topic in the applied evaluation literature. If there are unobserved variables which affect assignment into treatment and the outcome variable simultaneously, a hidden bias might arise to which matching estimators are not robust. We address this problem with the bounding approach proposed by Rosenbaum (2002), where mhbounds allows the researcher to determine how strongly an unmeasured variable must influence the selection process in order to undermine the implications of the matching analysis.
Keywords: 330; matching; treatment effects; sensitivity analysis; unobserved heterogeneity; Schätztheorie; Sensitivitätsanalyse; Theorie; Statistical matching